Menciptakan Keterampilan Belajar Siswa Melalui Literasi, untuk Meningkatkan Hasil Belajar - Odi, Mas; Za’iem, Abdullah; Abror, Kanzil; Aini, Anisyah Fitrotul (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Literacy plays a crucial role in fostering effective learning skills in students, which directly influences their learning outcomes. Literacy in this context includes various types such as reading, writing, numeracy, and digital literacy, providing a foundation for students to develop critical, analytical, and creative thinking skills. By implementing integrated literacy programs in education, students gain not only knowledge but also the skills to access, understand, and process information independently. This helps students face increasingly complex learning challenges in the 21st century. Therefore, literacy functions not only as a tool for acquiring information but also as a foundation for building broader and deeper learning skills. Furthermore, the application of digital literacy in learning offers students the opportunity to utilize technology to enhance their abilities. A comprehensive literacy concept, including the culture of school literacy, can improve the quality of learning and create an environment that supports students' skill development. Overall, efforts to cultivate learning skills through literacy play a significant role in facilitating improved learning outcomes for students at various educational levels.